2018
DOI: 10.1117/1.jbo.23.1.010503
|View full text |Cite
|
Sign up to set email alerts
|

Flexible nine-channel photodetector probe facilitated intraspinal multisite transcutaneous photobiomodulation therapy dosimetry in cadaver dogs

Abstract: Abstract. Noninvasive photobiomodulation therapy (PBMT) of spinal cord disease remains speculative due to the lack of evidence for whether photobiomodulatory irradiances can be transcutaneously delivered to the spinal cord under a clinically acceptable PBMT surface irradiation protocol. We developed a flexible nine-channel photodetection probe for deployment within the spinal canal of a cadaver dog after hemilaminectomy to measure transcutaneously transmitted PBMT irradiance at nine sites over an eight-cm spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…PBM treatment has demonstrated a beneficial effect on the prognosis of SCI animals in prior preclinical studies, 93,94 In this study, we found that PBM could have an inhibitory effect on NP after SCI by interfering with the NF-κB pathway and glial cell polarization, whereas the specific pathways may require further investigation. Since cytochrome C oxidase (CCO) has a distinct absorption band at 810 nm (near-infrared red light region), 96 the regulation on CCO might be the potential mechanism for 810 nm-PBM irradiation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…PBM treatment has demonstrated a beneficial effect on the prognosis of SCI animals in prior preclinical studies, 93,94 In this study, we found that PBM could have an inhibitory effect on NP after SCI by interfering with the NF-κB pathway and glial cell polarization, whereas the specific pathways may require further investigation. Since cytochrome C oxidase (CCO) has a distinct absorption band at 810 nm (near-infrared red light region), 96 the regulation on CCO might be the potential mechanism for 810 nm-PBM irradiation.…”
Section: Discussionmentioning
confidence: 66%
“…PBM treatment has demonstrated a beneficial effect on the prognosis of SCI animals in prior preclinical studies, 93,94 Reports have shown that PBM irradiation reduces the production of inflammatory factors, modulates the M1/M2 phenotypic polarization balance of immune cells, rescues the death of neurons, and promotes axonal regeneration and functional recovery. However, systematic clinical validation of the PBM intervention for NP in patients with SCI is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Piao el al. [12] also showed that on-contact surface irradiation increased the transmitted light by 67% compared with off-contact surface irradiation. Conversely, Krishna et al [13] monitored the rat weight in SCI contusion models, finding notable fluctuations in weight over the 14-day study; the weight increased within the first few days of the SCI as a result of water retention and then fell by 10-12% in the following 10 days.…”
Section: Introductionmentioning
confidence: 86%
“…These researchers assess the effectiveness of PBMT using the fluence ("dose") on the skin surface as the chief dose assessment index without considering the irradiation parameters or the physiological parameters of the animal's weight. Piao et al [12] recently demonstrated that the fluence rate, which reaches the targeted SCI area, depends on the tissue thickness at the injury site and the position of the probe relative to the injury site, that is, applying a certain level of fluence on the skin does not mean that the injury site will receive the same fluence rate. Piao el al.…”
Section: Introductionmentioning
confidence: 99%
“…Research on phototherapy for SCI in rat models revealed that percutaneous irradiation had an infrared transmittance of only 6% . Moreover, a study on percutaneous spinal cord irradiation in dogs revealed a transmittance of only 0.00102% . Such low transmittance values severely limit the practical application of phototherapy for SCI in humans.…”
Section: Introductionmentioning
confidence: 99%